Polyaniline photoluminescence quenching induced by single-walled carbon nanotubes enriched in metallic and semiconducting tubes - Mihaela Baibarac; Adelina Matea; Monica Daescu; Ionel Mercioniu; Sophie Quillard; Jean-Yves Mevellec; Serge Lefrant (Scientific Reports, 2018)
Abstract The influence of single-walled carbon nanotubes enriched in semiconductor (S-SWNTs) and metallic (M-SWNTs) tubes on the photoluminescence (PL) of polyaniline (PANI), electrosynthesized in the presence of the H2SO4 and HCl solutions, is reported. The emission bands peaked at 407–418 and 440–520 nm indicate that the electropolymerization of aniline (ANI) leads to the formation of short and longer macromolecular chains (MCs), respectively. We demonstrate that the reaction product consists of ANI tetramers (TT) and trimers (TR) as well as PANI-salt. Using Raman scattering and IR absorption spectroscopy, a covalent functionalization of SWNTs with shorter and longer MCs of PANI-salt is demonstrated. The presence of S-SWNTs and M-SWNTs induces a decrease in ANI TT weight in the reaction product mass consisting in S-SWNTs and M-SWNTs covalently functionalized with PANI-emeraldine salt (ES) and PANI-leucoemeraldine salt (LS), respectively. A PANI PL quenching is reported to be induced of the S-SWNTs and M-SWNTs. A de-excitation mechanism is proposed to explain PANI PL quenching.